Hospital physicians’ drugs prescription adherence to the essential drugs list of Bangladesh - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Rathor, Mohammad Yousuf; Md Aris, Mohd Aznan; Jabbar, Md. Abdul; Mazumder, Saroj Kumar (Centre for Promoting Ideas, USA, 2012)
Objective: This descriptive cross sectional study examined the existing pattern of hospital physicians’ drugs prescription adherence to the Essential Drugs List of Bangladesh. Background: The problem of hospital physicians’ drug prescription non-adherence to the Essential Drug List of Bangladesh is a considerable issue. Methods: This cross sectional study was conducted at outpatient departments of multiple health facilities of different levels: primary to tertiary A total of 920 patients were interviewed and their treatment profiles were examined. Results: The most commonly prescribed drugs were paracetamol, chlorpheniramine, vitamin B complex, amoxicillin, antacid, metronidazole, ciprofloxacin and cotrimoxazole. A notable proportion of prescribed drugs (20.8%) was not in the Essential Drugs List of Bangladesh. Conclusion: Non-adherence to the Essential Drug List reflects that the existing Essential Drugs List of Bangladesh is not comprehensive enough to serve the peoples’ needs and demands at large. Keywords: Physicians, Adherence, Essential Drug List, Bangladesh